2007
DOI: 10.1121/1.2942670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a large volume spherical resonator for studies of acoustically induced cavitation in liquids

Abstract: This paper describes a spherical acoustical resonator system used to study acoustic cavitation phenomena in liquids as part of an effort to scale up the energy density of collapse of transient cavitation. The resonator is formed by a stainless steel spherical shell 24.1 cm in diameter (OD) and either 1.27 cm or 1.90 cm thick designed for generating transient cavitation at high static pressures. An external transducer attached to the surface of the resonator was used to excite an acoustic standing wave in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…(1) at driving amplitudes much lower than those used to initiate cavitation. 16 Furthermore, the maximum pressure anti-node at r ¼ 0 was found to be linear with the driving amplitude near the cavitation threshold, as described in Ref. 17.…”
Section: Acoustic Resonatormentioning
confidence: 85%
See 1 more Smart Citation
“…(1) at driving amplitudes much lower than those used to initiate cavitation. 16 Furthermore, the maximum pressure anti-node at r ¼ 0 was found to be linear with the driving amplitude near the cavitation threshold, as described in Ref. 17.…”
Section: Acoustic Resonatormentioning
confidence: 85%
“…Since the quality factor of the system was so large, it was critical that the system be continuously driven at resonance. 16 This was accomplished by the use of a custom-designed phase locked loop (PLL) manufactured by IDI.…”
Section: Cavitation Generation Electronicsmentioning
confidence: 99%
“…A spherical acoustical resonator system used to study acoustic cavitation phenomena in liquids has been previously reported. 1 An external transducer attached to the surface of the resonator was used to excite an acoustic standing wave in the liquid. A similar resonator system exhibited transient acoustic cavitation in water at static pressures up to 300 bars.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the circles "*" and the boxs "h" are calculated using the empty shell and the rigid boundary limits, respectively. The(2,4),(6,1), and (7,1) modes are classified as elastic while the rest of the modes shown here are classified as acoustic.…”
mentioning
confidence: 99%